Antitumor and antimetastatic activities of vaccine prepared from cisplatin-resistant lewis lung carcinoma - Potebnya, G.P.; Voeykova, I.M.; Lisovenko, G.S.; Cheremshenko, N.L.; Todor, I.M.; Yudina, O.Yu.; Kovtonyuk, O.V.; Chekhun, V.F. (Experimental Oncology, 2009)
To study antitumor and antimetastatic activities of antitumor vaccine (ATV) prepared from cisplatin (CP) sensitive and resistant strains of Lewis lung carcinoma (LLC). Methods: The inhibition of tumor growth, and the mean survival time of the tumor-bearing animals, the number and the volume of metastases were measured as the indices of ATV efficacy. The activity of cytotoxic T-lymphocytes and natural killer cells, peritoneal macrophages (Mph), the level of tumor necrosis factor and the total proteolytic activity of blood plasma (PA) were assessed. Results: ATV from CP resistant LLC prepared using cytolectin (CL) of В. subtilis В-7025 significantly inhibited growth of CP resistant tumors (by 52%) and increased mean survival time (MST) of animals (by 44.6%). The index of metastasis inhibition for ATV prepared from CP sensitive or resistant LLC was 154.5% and 227.0%, respectively. In all vaccine-treated animals, Mph activity was shown to be significantly increased. In spite of high antitumor and antimetastatic effects of ATV prepared from CP resistant LLC, PA in plasma of animals inoculated with CP resistant LLC was increased significantly upon vaccine administration.